Managing credit risk : the great challenge for global financial markets - Caouette, John B., 1944-; Caouette, John B., 1944- (Wiley, 2008)
There have been significant developments and changes to the world of credit risk management in recent years. Managing Credit Risk, Second Edition will touch upon all these changes, including a new emphasis on actively managing credit risk, the introduction of important regulatory changes, and the impact of hedge funds on the field of credit. In addition, this comprehensive Second Edition also includes important updates and expanded discussions of the techniques used to control credit risk, historical roots of credit management, consumer credit models, and the major industry players- Resumé vydavatel
Keywords: kreditní riziko; finanční rizika; finanční deriváty; credit risk; financial risks; derivative securities; elektronické knihy; monografie; electronic books; monographs